Hicotea : a Nightlights story - Alvarez, Lorena (Nobrow, 2021)
When a young girl named Sandy peeks inside an empty turtle shell, she finds herself in a magical new world filled with mysterious and wondrous art. But one of the paintings is incomplete, and it's up to Sandy to finish it before she returns to her own dimension.